An Updated Overview of the Emerging Role of Patch and Film-Based Buccal Delivery Systems - Shery Jacob; Anroop B. Nair; Sai H. S. Boddu; Bapi Gorain; Nagaraja Sreeharsha; Jigar Shah (MDPI AG, 2021)
Buccal mucosal membrane offers an attractive drug-delivery route to enhance both systemic and local therapy. This review discusses the benefits and drawbacks of buccal drug delivery, anatomical and physiological aspects of oral mucosa, and various in vitro techniques frequently used for examining buccal drug-delivery systems. The role of mucoadhesive polymers, penetration enhancers, and enzyme inhibitors to circumvent the formulation challenges particularly due to salivary renovation cycle, masticatory effect, and limited absorption area are summarized. Biocompatible mucoadhesive films and patches are favored dosage forms for buccal administration because of flexibility, comfort, lightness, acceptability, capacity to withstand mechanical stress, and customized size. Preparation methods, scale-up process and manufacturing of buccal films are briefed. Ongoing and completed clinical trials of buccal film formulations designed for systemic delivery are tabulated. Polymeric or lipid nanocarriers incorporated in buccal film to resolve potential formulation and drug-delivery issues are reviewed. Vaccine-enabled buccal films have the potential ability to produce both antibodies mediated and cell mediated immunity. Advent of novel 3D printing technologies with built-in flexibility would allow multiple drug combinations as well as compartmentalization to separate incompatible drugs. Exploring new functional excipients with potential capacity for permeation enhancement of particularly large-molecular-weight hydrophilic drugs and unstable proteins, oligonucleotides are the need of the hour for rapid advancement in the exciting field of buccal drug delivery.